2014
DOI: 10.1186/s12911-014-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a screening electronic alert tool for severe sepsis and septic shock in the emergency department

Abstract: BackgroundEarly recognition of severe sepsis and septic shock is challenging. The aim of this study was to determine the diagnostic accuracy of an electronic alert system in detecting severe sepsis or septic shock among emergency department (ED) patients.MethodsAn electronic sepsis alert system was developed as a part of a quality-improvement project for severe sepsis and septic shock. The system screened all adult ED patients for a combination of systemic inflammatory response syndrome and organ dysfunction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…To assist clinicians in detecting patients at risk of physiological instability clinical decision support and automation of warnings have been advocated [7,8]. Such systems have to rely on the data in the Electronic Health Record Systems (EHRs) to provide accurate warnings.…”
Section: Background and Significancementioning
confidence: 99%
“…To assist clinicians in detecting patients at risk of physiological instability clinical decision support and automation of warnings have been advocated [7,8]. Such systems have to rely on the data in the Electronic Health Record Systems (EHRs) to provide accurate warnings.…”
Section: Background and Significancementioning
confidence: 99%
“…The sensitivity and specificity of alerts has been a challenge when implementing an electronic reminding system for early detection of sepsis [14][15][16]. A unique feature of this study was examining the accuracy of alerts on medical-surgical units with patients at risk for varying levels of sepsis severity vs. previous studies conducted in the emergency department or ICUs or just with patients experiencing severe sepsis/ septic shock [14][15][16]. We found that sensitivity was 95.1% and specificity was 82% with the highest sensitivity for severely ill patients (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies implemented screening tools [13,14] while others included alerts based on patient parameters, order sets, and recommended interventions [10][11][12]14]. The sensitivity and specificity of alerts varied considerably across studies [14][15][16]. The higher rate of accurately detecting sepsis is associated with settings such as the emergency department or ICUs.…”
Section: Summary Of Multi-focal Interventions To Detect Sepsis and Immentioning
confidence: 99%
“…The test performance of these alerts may provide one reason for their limited success. Using physician orders in the emergency department may improve specificity of an EHR alert system, but physician orders have not been utilized to represent infection in published sepsis alerts [18][19].…”
Section: Introductionmentioning
confidence: 99%